2020
DOI: 10.1038/s41598-020-68639-2
|View full text |Cite
|
Sign up to set email alerts
|

Ascites-induced compression alters the peritoneal microenvironment and promotes metastatic success in ovarian cancer

Abstract: The majority of women with recurrent ovarian cancer (OvCa) develop malignant ascites with volumes that can reach > 2 L. The resulting elevation in intraperitoneal pressure (IPP), from normal values of 5 mmHg to as high as 22 mmHg, causes striking changes in the loading environment in the peritoneal cavity. The effect of ascites-induced changes in IPP on OvCa progression is largely unknown. Herein we model the functional consequences of ascites-induced compression on ovarian tumor cells and components of the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 58 publications
2
43
0
Order By: Relevance
“…In agreement with studies by Dr. Stack, TnTs were not found in mesothelial-tumor cell co-cultures in the absence of external pressure. In their studies, it was found that compression increased TnT formation between peritoneal cells and tumor cells [ 29 ]. Ongoing studies suggest that mesothelial/OCC induce production of FGFs and EGF growth factors in mesothelial cells that may create a paracrine loop that enables tumor cell growth and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with studies by Dr. Stack, TnTs were not found in mesothelial-tumor cell co-cultures in the absence of external pressure. In their studies, it was found that compression increased TnT formation between peritoneal cells and tumor cells [ 29 ]. Ongoing studies suggest that mesothelial/OCC induce production of FGFs and EGF growth factors in mesothelial cells that may create a paracrine loop that enables tumor cell growth and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the application of mechanical compression on living cells, such as cancerous [5,[9][10][11][12][13][14][15][16][17][18][19], non-cancerous and stromal cells [20][21][22], neurons [23] and chondrocytes [24], has gained importance in recent years. Compression applied on cancer types, such as breast [5,16,18,19], brain [13], pancreatic [9] and ovarian [17,25] cancer cells, resulted in more invasive and metastatic forms. While indicative, previous studies all point out the need for further investigations to understand the e↵ect of compressive mechanical stimuli in metastasis of di↵erent cancer types, for example ovarian cancer [17,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Asem et al [25] and Klymenko et al [27] applied static compression at ⇠3 kPa and at 3.18-3.53 kPa, respectively, on ovarian cancer models in o↵-chip settings. On the other hand, a recent work by Novak et al remains the only study to date using a bioreactor device, which is yet at millimeter scale, to investigate the e↵ect of compressive mechanical stress on ovarian cancer [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations